A Systematic Literature Review of College and Career Readiness Frameworks for Students With Disabilities. (December 2020) - Monahan, Jessica L.; Lombardi, Allison; Madaus, Joseph; Carlson, Sarah R.; Freeman, Jennifer; Gelbar, Nicholas
A systematic review was conducted to understand the extent of empirical support for College and Career Readiness (CCR) frameworks and whether or not students with disabilities (SWD) are included in these frameworks. We identified 26 articles that showed a complex set of domains with both academic and nonacademic skills. Findings showed few studies reported empirical research concerning CCR frameworks for SWD and there was a strong emphasis on college and academic outcomes. Suggestions for future research include studies that further support or identify areas of weakness in proposed CCR frameworks, better clarification of CCR nonacademic skills, and the development of accompanying measures to broaden the understanding of CCR and ultimately inform policy and practice.